2022
DOI: 10.13057/biodiv/d230928
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of wild spice plants of the Central Kazakhstan region and their medicinal potential

Abstract: Abstract. Pozdnyakova Y, Omarova G, Murzatayeva A, Tankibaeva N. 2022. Biodiversity of wild spice plants of the Central Kazakhstan region and their medicinal potential. Biodiversitas 23: 4609-4625. The Central Asian region stretches from the Caspian Sea in the west to the border of western China in the east. Central Kazakhstan occupies the space of steppe and semi-desert zones within the Turgay Plateau in the west and the Kazakh Uplands in the center and in the east. Due to the remoteness of the steppes of Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 129 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…The knowledge on medicinal plants and fungi mixed in magical rituals and customs is mostly preserved in those areas with logistically or financially difficult access to a doctor or veterinarian (Howes et al, 2020). A considerable body of literature covers interesting studies from high mountains (e.g., Tucakov, 1997;Pullaiah et al, 2017;Petelka et al, 2020), from steppe and grassland landscapes (e.g., Molares and Ladio, 2009;Pozdnyakova et al, 2022;Santoro et al, 2022) to from more or less pristine forests (e.g., Uprety et al, 2012;Rodrigues et al, 2021;Kolosova et al, 2022). Old herbal scripts in monasteries showed that herbalists have been always part of the medicinal landscape, even in easily accessible regions before the advent of conventional medicine (Green, 1989;Sabatini, 1994), but were pushed back there more quickly, despite many conventional drugs being developed based on natural remedies (Clément, 2005;Pan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge on medicinal plants and fungi mixed in magical rituals and customs is mostly preserved in those areas with logistically or financially difficult access to a doctor or veterinarian (Howes et al, 2020). A considerable body of literature covers interesting studies from high mountains (e.g., Tucakov, 1997;Pullaiah et al, 2017;Petelka et al, 2020), from steppe and grassland landscapes (e.g., Molares and Ladio, 2009;Pozdnyakova et al, 2022;Santoro et al, 2022) to from more or less pristine forests (e.g., Uprety et al, 2012;Rodrigues et al, 2021;Kolosova et al, 2022). Old herbal scripts in monasteries showed that herbalists have been always part of the medicinal landscape, even in easily accessible regions before the advent of conventional medicine (Green, 1989;Sabatini, 1994), but were pushed back there more quickly, despite many conventional drugs being developed based on natural remedies (Clément, 2005;Pan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%